Upcycling of waste polycarbonate into polyallyls for degradable high-performance BMI/polyallyl-based thermosets/CFRPs - Che-Wei Lin; Lu-Ling Chen; Dula Daksa Ejeta; Ching-Hsuan Lin (Chemical Engineering Journal, 2026)

Interface-decoupled oxygen reduction via atomic Pt–Pd–Co clusters and vacancy-mediated kinetic buffering in a hierarchical carbon-supported multimetallic oxide platform - Yang-Yang Hsu; Ching-Hua Fan; Yu-Lin LEE; Sheng Dai; Kuan-Wen Wang; Nozomu Hiraoka; Hirofumi Ishii; Ting-Shan Chan; Chia-Shing Wu; Guo-Wei Lee; Po-Chun Chen; Tsan-Yao Chen (Chemical Engineering Journal, 2026)

Piezo-coupled triboelectric self-powered tactile sensor based on a self-healable polymer for object recognition - Manikandan Venkatesan; Wei-Wen Chen; Yu-Chen Wang; Yung-Chi Hsu; Jayashree Chandrasekar; Hao-Yuan Chen; Shih-Yu Lin; Chia-Jung Cho; Shang-Jui Huang; Ming-An Chung; Wen-Ya Lee; Yu Wen; et al. (Chemical Engineering Journal, 2026)

First visualization of intact sperm storage tubules in the duck oviduct: A fluorescent labeling approach for targeted SST sampling - Hsiu-Lien Herbie Lin; Chin-Hui Su; Shih-Yi Huang; Ya-Hsin Kuo; Liang-Yuan Wei; Yi-Ying Chang; Ching-Wei Chang; Jeng-Fang Huang; Pascal Mermillod; Chih-Hsiang Cheng (Animal Reproduction Science, 2026)

Biomass-inherent nitrogen doping in utilized chopsticks carbon for alkaline electrolysis - PratimaDevi Sivasubramanian; Yen-Ping Peng; Po-Hsun Lin; Subramanian Sakthinathan; Te-Wei Chiu; Ching-Lung Chen (Biomass and Bioenergy, 2026)

Plant–soil feedback persists beyond host death to shape density-dependent plant competition - Ching-Lin Huang; Joe Wan; Shuo Wei; Chia-Hao Chang-Yang; Po-Ju Ke (Plant and Soil, 2026)

Circular bioprocessing of bovine blood for peptide-based antimicrobial and antibiofilm agents - Gan Huey; Asif Ali Bhat; Bao-Hong Lee; Ming‐Kuei Shih; Li-Jung Yin; You-Lin Tain; Yu-Wei Chen; Yeu-Ching Shi; Chih-Yao Hou (Bioresource Technology, 2026)

First complete coding sequence of ovine herpesvirus 2 from a malignant catarrhal fever case of Formosan sambar deer in Taiwan: Genomic characterization and molecular epidemiology - Ruei-Sheng Tsai; Shih-Te Chuang; Hau-You Tzeng; Fong-Yuan Lin; Ching-Yu Tseng; Yi-Chen Chen; Wei-Li Hsu (The Veterinary Journal, 2026)

Application of a novel complex surfactant to enhance the bioremediation of weathered-diesel oil contaminated soils: mechanism and mesocosm-scale study - Wei-Ting Chen; Jiun-Hau Ou; Wei-Zhe Lin; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Soils and Sediments, 2026)

Novel DUAL Z-SCHEME Bi2MoO6/SO3H@g-C3N4/ZnS photocatalyst enhanced by persulfate activation for rapid ofloxacin degradation: Integrated experimental and DFT studies - Imran Nasir Appau Zahir Hussain; Sanjay Ballur Prasanna; Po-Chun Chen; Yu-Chien Lin; Ching-Wei Tung; Ren-Jei Chung (Journal of Water Process Engineering, 2026)

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Improvement of indoor air quality and health effects in COPD patients in a heavy industrial area - Jia Lin Zhang; Yi Ting Chang; Ching Yu Hsiao; Chung-Shin Yuan; Yen-Ping Peng; Da Wei Wu; Huang-Chi Chen; Jia-Yu Kuo; Huai-Lei Juan; Pei-Shih Chen (Environmental Research, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Melatonin suppresses glycolysis and coordinately disrupts DNA repair via targeting the YAP1-NAMPT signaling in breast cancer - Yi-Wen Lai; Cheng-Ying Chu; Zei-Wei Liu; Hsin-Ying Lu; Chi-Ching Lee; Mei-Hsiang Lin; Cheng-Wei Lin (Chemico-Biological Interactions, 2026)

Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Cu2Te/Au@rGO aerogel as an efficient electrocatalyst for the bimodal electrochemical-colorimetric detection of 4-nitrotoluene - Nandini Nataraj; Agalya Mahalingam; Xinke Liu; Yu-Chien Lin; Ching-Wei Tung; Hsu-Wei Fang; Ren-Jei Chung (Process Safety and Environmental Protection, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Quantification of the variability of the soil moisture field in response to variations in the rainfall field - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee; Wei-Cheng Lo (Journal of Hydrology, 2025)

Multifunctional visual photoelectrochemical sensor based on ternary Sb2WO6/P@g-C3N4/Ag2S nanocomposite for selective mercury-ion monitoring in environmental matrices and energy storage applications - Abishek Jayapaul; Sanjay Ballur Prasanna; Lu-Yin Lin; Rajalakshmi Sakthivel; Yu-Chien Lin; Ching-Wei Tung; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2025)

Nanoengineered scheelite-structured SrWO4 decorated on MXene sheets: A novel platform for electrochemical sensing of the anti-cancer drug nilutamide with DFT insights - Akash Ashokrao Jagtap; Vaibhav Kanke; Rajalakshmi Sakthivel; Amar S. Katkar; Lu-Yin Lin; Yu-Chien Lin; Xinke Liu; Cihun-Siyong Gong; Ching-Wei Tung; Ren-Jei Chung (Environmental Research, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Associations between parental shift work exposure and pregnancy outcomes: role of father’s shift work status - Chih-Fu Wei; Mei-Huei Chen; Ching-Chun Lin; Yueliang Leon Guo; Shio-Jean Lin; Ya-Wen Chen; Wu-Shiun Hsieh; Pau-Chung Chen (International Archives of Occupational and Environmental Health, 2025)

Characterization of temporal nonstationary random soil moisture perturbation fields - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee; Wei-Cheng Lo (Advances in Water Resources, 2025)

Fluoride removal from groundwater via powder-nano MgO adsorption: novel adsorbents development and mechanisms studies novel adsorbents development and mechanisms studies - Jiun-Hau Ou; Ssu-Ching Chen; Wei-Zhe Lin; Francis Verpoort; Rao Y. Surampalli; Chih-Ming Kao (Environmental Science and Pollution Research, 2025)

The influence of trees shade level on human thermal comfort and the development of applied assessment tools - Yu-Ying Wei; Ching-Yin Cheng; Tzu-Ping Lin (Landscape and Urban Planning, 2025)

Entropy-stabilized multi-element 2D TMDs: Tunable electronics and enhanced thermal stability - Ching-Wei Chin; Chong-Chi Chi; Kai-Yuan Hsiao; Yi-Hsin Fang; Dun-Jie Jhan; Chun-Hui Lin; Ming-Pei Lu; Ming-Yen Lu (Chemical Engineering Journal, 2025)

Fabrication of superwetting gelatin/phytic acid/cellulose composites with antibacterial characteristics for separating complex contaminants from wastewater - Guyita Berako Belachew; Chien-Chieh Hu; Chih-Feng Wang; Mei-Yi Liao; Wei-Song Hung; Ching-Hsuan Lin; Shiao-Wei Kuo; Juin-Yih Lai (Journal of Water Process Engineering, 2025)

Enhanced electrochemical nitrate reduction: Geometrically tailored Pd/Cu electrodes for superior nitrogen selectivity - Thi Nhat-Tuyen Nguyen; Kiruthika Mariappan; Muhammad Sheraz Ahmad; Feng-Ze Tian; Ching-Wei Tung; Jenn Fang Su; Chao-Lin Liu; Ching-Lung Chen (Journal of Environmental Chemical Engineering, 2025)

High-sensitivity Ara h1 detection with a praseodymium niobate-carbon nanofiber immunosensor - Evangeline Jafneel Nixon; Rajalakshmi Sakthivel; Yu-Chien Lin; Hsiao-Wei Wen; Ching-Wei Tung; Ren-Jei Chung (Food Chemistry, 2025)

Exploring PFRs, ROS, PAHs, nitro-PAHs, and health risks of the nonthermal plasma intervention size-segregated smoldering incense and mosquito coils aerosols - Yu-Chieh Wang; Chia C. Wang; Chon-Lin Lee; Wei-Min Ching (Environmental Pollution, 2025)

Causes, emission characteristics, and health risks of persistent free radicals and reactive oxygen species in PM2.5 produced by smoldering incense - Yu-Chieh Wang; Bo-Yu Chen; Yen-Hsien Li; Tzu-Hsien Tseng; Chon-Lin Lee; Wei-Min Ching (Atmospheric Pollution Research, 2025)

Prenatal exposure to air pollution and pediatric acute leukemia: A nationwide study - Hsin-Chien Yen; I-Chieh Chen; Wei-Szu Lin; Kuan-Chia Lin; Meng-Che Wu; Ching-Heng Lin (Science of The Total Environment, 2025)

The environmentally relevant concentration of triclosan induces carbon dioxide emission in estuarine sediment associated with disrupted microbial metabolism - Chi-Wei Huang; Jia-En Cai; Ching-Lun Lin; Chin-Jou Wang (Marine Environmental Research, 2025)

Adaptive fluoride removal across concentration scales: Potential roles of microbial and acicular gypsum interactions in nitrogen and phosphate cycling - Ying-Liang Yu; Wei-Han Lin; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Hazardous Materials, 2025)

Development and Evaluation of a Dual-Mode Cold Atmospheric Plasma System for Stage-Specific Wound Healing Applications - Ching-Yuan Lin; Dong-Jin Li; Yu-Shen Chen; Chia-Wei Hsu; Mohd Yaqub Khan; Ming-Chen Wang (Journal of Medical and Biological Engineering, 2025)

Microplastic-induced hypertension in rats: A two-hit model exploring oxidative stress and gut microbiota - Yu-Chun Cheng; Wei-Ling Chen; Hong-Ren Yu; Ching-Yi Tsai; Jiunn-Ming Sheen; Mao-Meng Tiao; Chien-Ning Hsu; You-Lin Tain (NanoImpact, 2025)

Synergistic integration of dual Z-scheme Gd2Sn2O7/Ag3PO4/SnS2 heterojunction for accelerated visible-light photodegradation of sulfasalazine: Insights into DFT, toxicity, and antibacterial study - Akash Ashokrao Jagtap; Sanjay Ballur Prasanna; Susaritha Ramanathan; Sandeep Shadakshari; Kumara Swamy Ningappa; Yu-Chien Lin; Xinke Liu; Ching-Wei Tung; Ren-Jei Chung (Journal of Water Process Engineering, 2025)

Bifunctional approach for electrochemical detection and catalytic degradation of Rhodamine B in environmental samples using a NiFe2O4@C/PPy catalyst: Kinetic and thermodynamic insights - Mosas Vinsy Arul Thomas; Sanjay Ballur Prasanna; Akash Ashokrao Jagtap; Gagankumar Sakleshpur Kumar; Yu-Chien Lin; Rajalakshmi Sakthivel; Ching-Wei Tung; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2025)

3D printed microtissue cassettes enabling high throughput proton radiobiological assays - Chih-Tsung Yang; I-Chun Cho; Ching-Fang Yu; Edward Cheah; Tesi Liu; Yi-Ping Lin; Sing-Yu Hu; Jyun-Wei Jheng; Ivan Kempson; Tsi-Chian Chao; Sen-Hao Lee; Eva Bezak; et al. (Analytica Chimica Acta, 2025)

Pixel array-based urine biosensor for detection of trimethylamine N-oxide and glucose for early detection of diabetic kidney disease - Mei-Ching Yu; Chi-Jen Lo; Wei-Cheng Lin; Wei-Lun Yen; Yun-Yu Hsieh; Bing-Hong Chen; Fu-Sung Lo (Analytica Chimica Acta, 2025)

BTEX exposure and metabolite levels in Taiwan schoolchildren near petrochemical areas - Wei-shan Chin; Ching-chun Huang; Yu-cheng Chen; Jing-fang Hsu; Chih-Da Wu; Pinpin Lin; Pau-chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Rapid evaluation of apigenin bioavailability and hypouricemic bioactivity by targeted metabolomics study in enterohepatic microenvironment mimetic cell culture model - Su-Jung Hsu; Hui-Chen Chung; Chia-Hsuan Chang; Yi-Chi Liao; Ta-Wei Liu; Shu-Mei Lin; Ching-Kuo Lee (Food Research International, 2025)

Elevated Reproductive Risk and Toxicity of Triclosan in Urban Freshwater Environments after the COVID- 19 Pandemic - Ching-Lun Lin; Chi-Wei Huang (Water, Air, & Soil Pollution, 2025)

ONC201 exerts oncogenic effects beyond its mitochondria-disturbing role in neuroblastoma subsets - Jyun-Hong Jiang; Yu-Han Lin; Pei-Lin Liao; Ting-Ya Chen; Hui-Ching Chuang; Chao-Cheng Huang; Wen-Ming Hsu; Jiin-Haur Chuang; Wei-Shiung Lian (Journal of Molecular Medicine, 2025)
Neuroblastoma (NB) is a formidable challenge in pediatric oncology due to its intricate molecular landscape, necessitating multifaceted therapeutic approaches. ONC201 is an imipridone antibiotic compound with a promising drug candidate leveraging its potent anticancer properties against the mitochondrial proteases ClpP and ClpX. Despite demonstrating early clinical promise, particularly in MYCN -amplified NB, its efficacy in non- MYCN -amplified NB remains a subject worthy of investigation. In this study, we extended the coverage of ONC201 to treat non- MYCN -amplified NB, and our data implicated ONC201’s inability to reduce tumor growth in animal models harboring SK-N-AS or SK-N-FI cell lines. Interestingly, ONC201 induced the expression of oncogenic markers c-Myc and LGR5 while downregulating the tumor suppressor ATRX. While it fails to attenuate tumor neovascularization in non- MYCN -amplified NB xenografts, its effectiveness differs from that of its MYCN-amplified counterpart. Rho zero (ρ0)-SK-N-AS cells treated with ONC201 showed comparable observed trends in parental SK-N-AS cells, including LGR5 upregulation and ATRX downregulation, suggesting that ONC201’s multifaceted actions extend beyond mitochondrial targets. Our elucidation highlights the need to discern molecular signatures when deploying ONC201 monotherapy against NB, which lacks MYCN- amplification.

Establishment of a pseudotargeted LC‒MS/MS workflow for analyzing triglycerides in biological samples - Wei-Chieh Wang; Chin-Yi Wang; Ta-Chen Su; Po-Chih Lin; Wen-Chi Chang; Kuei-Pin Chung; Ching-Hua Kuo (Analytica Chimica Acta, 2025)

Surveillance and genetic diversity of bovine viral diarrhea virus in dairy herds across Taiwan - Fong-Yuan Lin; Hau-You Tzeng; Ching-Yu Tseng; Ruei-Sheng Tsai; Mami Oba; Tetsuya Mizutani; Yumiko Yamada; Hue-Ying Chiou; Shih-Te Chuang; Wei-Li Hsu (The Veterinary Journal, 2025)

Dynamic vertical land motion driven by climate and humans in the metropolitan Taipei Basin - Pei-Chin Wu; Meng (Matt) Wei; Jyr-Ching Hu; Steven D'Hondt; Hsin Tung; Shao-Hung Lin; Christopher J. Russoniello (Remote Sensing Applications: Society and Environment, 2025)

Displacement evolution of failure and non-failure sliding rock slopes - Hsien-Li Kuo; Guan-Wei Lin; Ting-Yu Lin; Che-Hsin Liu; Chung-Ray Chu; Chih-Hsin Chang; Ching-Weei Lin; Hongey Chen (Landslides, 2025)

The herbicide 2,4-dichlorophenoxyacetic acid induces pancreatic β-cell death via oxidative stress-activated AMPKα signal downstream-regulated apoptotic pathway - Ken-An Lin; Chin-Chuan Su; Kuan-I Lee; Shing-Hwa Liu; Kai-Min Fang; Chih-Hsin Tang; Wei-Cheng Lia; Chun-Ying Kuo; Kai-Chih Chang; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology Letters, 2025)

Artificial digestion represents the worst-case scenario for studying nanoplastic fate in gastrointestinal tract - Giselle Lee; Ya-Jhu Jhang; Yu-Tung Jhang; Yen-Chen Chang; Hui-Wen Chang; Chun-Yu Chuang; Yung-Kun Chuang; Ching-Wei Lin; I-Lun Hsiao (Journal of Hazardous Materials, 2025)

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Ambient stable ZnBr2-assisted lead-free perovskite for enhanced piezoelectricity of polyvinylidene fluoride in versatile piezo-phototronic applications - Manikandan Venkatesan; Wei-Chun Lin; Wei-Cheng Chen; Jayashree Chandrasekar; Yu-Hang Huang; Kai-Wei Lin; Zih-Syuan Syu; Ja-Hon Lin; Wei-Hung Chiang; Wei-Ren Liu; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2025)

Using Gaussian Mixture Model Clustering for the Automated Segmentation of Cerebral Arteriovenous Malformations in Magnetic Resonance Images - Ting-Yu Lin; Cheng‑Chia Lee; Yu-Wei Chen; Hsiu-Mei Wu; Ching-Jen Chen; Huai-Che Yang; Syu-Jyun Peng (Journal of Medical and Biological Engineering, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Unraveling the heterogeneous hydrogeological characteristics in the Choushui River alluvial fan, Taiwan, through observations from the multi-layer compaction monitoring wells - Reyhan Azeriansyah; Kuo-En Ching; Cheng-Wei Lin; Kuo-Chin Hsu; Pei-Ching Tsai; Chao-Lung Yeh; Ruey-Juin Rau (Engineering Geology, 2025)

Deep learning in the advanced core sample porosity determination with XCT image - Hung-Yu Wu; Ching-Li Kuo; Chen-Yi Lin; Wei-Ta Chu (Earth Science Informatics, 2025)

Nanoplastics indirectly compromise lettuce growth in hydroponic systems via microbial extracellular vesicles derived from Curvibacter fontanus - Bao-Hong Lee; Yi-Ching Lin; Yu-Juan Zheng; Tang-Long Shen; Ting-Yu Cheng; Chih-Chia Huang; Wei-Hsuan Hsu (Journal of Hazardous Materials, 2024)

A ratiometric turn-on chemosensor for highly selective and sensitive visual detection of Zn2+ and its applications to environmental samples - Keerthika Kumarasamy; Zhe-Wei Wu; Wei-Jyun Chien; Mei-Ching Lin; Selva Kumar Ramasamy (Journal of Environmental Chemical Engineering, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

In enzymatic reactions, the reverse reaction reduces product noise - Ching-Chu Hsieh; Yung-Chun Lin; Wei-Bo Lin; Che-Chi Shu (BioSystems, 2024)

Dissecting the temporal genetic networks programming soybean embryo development from embryonic morphogenesis to post-germination - Yen-Ching Wang; Wei-Hsun Hsieh; Liang-Peng Lin; Meng-Hsun He; Ya-Ting Jhan; Chu-Jun Huang; Junpeng Zhan; Ching-Chun Chang; Tzung-Fu Hsieh; Jer-Young Lin (Plant Cell Reports, 2024)

Health risks of environmentally persistent free radicals in atmospheric particulate matter during the spring festival travel season in Tainan, Taiwan - Yu-Chieh Wang; Wei-Min Ching; Chon-Lin Lee (Environmental Science and Pollution Research, 2024)

Development of Quantitative Norms for Normal Lung Uptake Based on Three-Dimensional Gallium-67 Single Photon Emission Computed Tomography/Computed Tomography - Tzyy-Ling Chuang; Wei-Lin Li; Yu-Ching Hs; Jyh-Cheng Chen; Yuh-Feng Wang (Journal of Medical and Biological Engineering, 2024)
Purpose Gallium-67 (Ga-67) lung scans assess alveolitis and interstitial lung disease, with Ga-67 accumulation correlating with inflammation intensity as seen in lung biopsy sections. Both semi-quantitative and quantitative methods have been used, with the latter providing an inflammatory activity index linked to lung lavage and histopathological scores. However, differing reference points result in varying outcomes. This study aimed to establish standard Ga-67 index parameters using semi-quantitative analysis and a linear regression model based on planar and SPECT/CT images. Methods Twenty subjects without lung disease received a 5–6 mCi Ga-67 injection via the ankle. Both planar and SPECT/CT images were analyzed, with semi-quantitative values assessed using GraphPad Prism 9.5.1. Results Compared to planar images, SPECT/CT acquisitions for the lung-to-arm uptake ratio proved the most reliable indicator for assessing lung inflammation. Increased lung Ga-67 uptake was defined as greater than 2 standard deviations from the average Ga-67 uptake for healthy subjects. The normal range was 0.065 ± 0.049 for the right side and 0.076 ± 0.070 for the left side. Conclusion Lung-to-arm ratios in SPECT/CT images are more accurate than those in planar images. This method should be adopted as a standard clinical practice, providing more reliable diagnostic information and improving patient management. Future studies should compare patients without lung disease to those with lung disease to determine the diagnostic benefit of these norms.

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Study on the performance of highly doped copper tailings sand for concrete pavements using specific grading techniques - Sung-Ching Chen; Meng-Yao Gao; Wei-Ting Lin; Le-Ping Liu; Kinga Korniejenko (Minerals Engineering, 2024)

Metal-organic framework derived Mn0.2Zn0.8Se/C amalgamated with nitrogen-doped graphene hydrogel for antioxidant trolox detection in food, environmental, and biological samples - Akash Ashokrao Jagtap; Rajalakshmi Sakthivel; Subbiramaniyan Kubendhiran; Lu-Yin Lin; Sayee Kannan Ramaraj; Xinke Liu; Dhanaprabhu Pattappan; Hsu-Wei; Yi-Ting Lai; Ching-Wei Tung; Ren-Jei Chung (Chemical Engineering Journal, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

Design of a pebbles-like erbium stannate integrated with graphene nanoribbons for the anti-cancer drug nilutamide detection in water and biological samples - Abishek Jayapaul; Rajesh Kumar Panda; Sayee Kannan Ramaraj; Lu-Yin Lin; Yeh-Fang Duann; Yu-Chien Lin; Yu-Chun Lu; Wai-Ching Liu; Ching-Wei Tung; Rajalakshmi Sakthivel; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2024)

Surface ligand engineering of perovskite quantum dots for n-type and stretchable photosynaptic transistor with an ultralow energy consumption - Wei-Cheng Chen; Yan-Cheng Lin; Zih-Syuan Syu; Ya-Shuan Wu; Kai-Wei Lin; Cheng-Liang Liu; Chi-Ching Kuo; Wen-Chang Chen (Chemical Engineering Journal, 2024)

Predicting ischemic stroke patients’ prognosis changes using machine learning in a nationwide stroke registry - Ching-Heng Lin; Yi-An Chen; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Wei-Lun Chang; Yang C. Fann; Kai-Cheng Hsu; Jiunn-Tay Lee (Medical & Biological Engineering & Computing, 2024)
Accurately predicting the prognosis of ischemic stroke patients after discharge is crucial for physicians to plan for long-term health care. Although previous studies have demonstrated that machine learning (ML) shows reasonably accurate stroke outcome predictions with limited datasets, to identify specific clinical features associated with prognosis changes after stroke that could aid physicians and patients in devising improved recovery care plans have been challenging. This study aimed to overcome these gaps by utilizing a large national stroke registry database to assess various prediction models that estimate how patients’ prognosis changes over time with associated clinical factors. To properly evaluate the best predictive approaches currently available and avoid prejudice, this study employed three different prognosis prediction models including a statistical logistic regression model, commonly used clinical-based scores, and a latest high-performance ML-based XGBoost model. The study revealed that the XGBoost model outperformed other two traditional models, achieving an AUROC of 0.929 in predicting the prognosis changes of stroke patients followed for 3 months. In addition, the XGBoost model maintained remarkably high precision even when using only selected 20 most relevant clinical features compared to full clinical datasets used in the study. These selected features closely correlated with significant changes in clinical outcomes for stroke patients and showed to be effective for predicting prognosis changes after discharge, allowing physicians to make optimal decisions regarding their patients’ recovery. Graphical Abstract

A Ce2MgMoO6 double perovskite decorated on a functionalized carbon nanofiber nanocomposite for quantification of ciprofloxacin in milk and honey samples: Density functional theory interpretation - Akash Ashokrao Jagtap; Sanjay Ballur Prasanna; Gagankumar Sakaleshpur Kumar; Yu-Chien Lin; Udesh Dhawan; Yu-Chun Lu; Rajalakshmi Sakthivel; Ching-Wei Tung; Ren-Jei Chung (Chemosphere, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

Protective Effects of Roselle Aqueous Extracts against UV-Induced Damage in Zebrafish Fins - I-Ting Lee; Ching-Yuan Huang; Wei-Lin Su; Tran M. Truong; Chi-Chung Wen; Bo-Chang Wang; Yau-Hung Chen (Fishes, 2024)
(1) Background: Roselle (Hibiscus sabdariffa) is a flowering plant reported to have anti-obesity, antioxidant, antibacterial, and anti-inflammatory effects. This study aims to evaluate the UV-absorbing and antioxidant activities of roselle aqueous extracts (RAE) and test the protective effects of RAE against UV radiation in zebrafish embryos. (2) Methods: DPPH assay and UV-spectrum methods were applied to evaluate the antioxidant and UV-absorbing activities, respectively. The protective effects of RAE were evaluated using fin morphology recording, Kaplan–Meier analysis, and Cox proportional hazards regression. Real-time PCR experiments were also applied to detect both the UV- and RAE-induced gene expressions. (3) Results: Our results show that (i) RAE had UV-absorbing abilities and significantly reduced ROS production in vitro; (ii) the mean times of malformed fins in the UV + RAE (36 and 48 ppm) groups were 3.56 and 4.44 days, respectively, and were prolonged compared to those in the UV-only group (3.36 days); (iii) zebrafish in the UV + RAE (36 and 48 ppm) groups were 0.963 and 0.496 (p

Quantifying payloads of antibody‒drug conjugates using a postcolumn infused-internal standard strategy with LC‒MS - Chih-Ning Cheng; Hsiao-Wei Liao; Ching-Hung Lin; Wen-Chi Chang; I-Chun Chen; Yen-Shen Lu; Ching-Hua Kuo (Analytica Chimica Acta, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Different microbial communities in paddy soils under organic and nonorganic farming - Jimmy Kuo; Daniel Liu; Wei Hao Wen; Ching Yuan Chiu; Wanyu Chen; Yun Wen Wu; Fang-Ting Lai; Chorng-Horng Lin (Brazilian Journal of Microbiology, 2024)

Macular pigments produced from microalga Chlorella sp. and applied to alleviate the pathogenic process in diabetic mice - Meng-Wei Lin; Wei-Hong Chiu; Cheng-Han Lin; Dung-Huan Liu; Pei-Ching Wu; Chih-Sheng Lin (Algal Research, 2024)

Probing the hair detectability of prohibited substances in sports: an in vivo-in silico-clinical approach and analytical implications compared with plasma, urine, and faeces - Shao-Hsin Hung; Hung-Lin Kan; Chun-Wei Tung; Yi-Ching Lin; Ting-Ting Chen; Ciao Tian; William Chih-Wei Chang (Archives of Toxicology, 2024)
Hair analysis is a crucial method in forensic toxicology with potential applications in revealing doping histories in sports. Despite its widespread use, knowledge about detectable substances in hair is limited. This study systematically assessed the detectability of prohibited substances in sports using a multifaceted approach. Initially, an animal model received a subset of 17 model drugs to compare dose dependencies and detection windows across different matrices. Subsequently, hair incorporation data from the animal experiment were extrapolated to all substances on the World Anti-Doping Agency’s List through in-silico prediction. The detectability of substances in hair was further validated in a proof-of-concept human study involving the consumption of diuretics and masking agents. Semi-quantitative analysis of substances in specimens was performed using ultra-performance liquid chromatography–tandem mass spectrometry. Results showed plasma had optimal dose dependencies with limited detection windows, while urine, faeces, and hair exhibited a reasonable relationship with the administered dose. Notably, hair displayed the highest detection probability (14 out of 17) for compounds, including anabolic agents, hormones, and diuretics, with beta-2 agonists undetected. Diuretics such as furosemide, canrenone, and hydrochlorothiazide showed the highest hair incorporation. Authentic human hair confirmed diuretic detectability, and their use duration was determined via segmental analysis. Noteworthy is the first-time reporting of canrenone in human hair. Anabolic agents were expected in hair, whereas undetectable compounds, such as peptide hormones and beta-2 agonists, were likely due to large molecular mass or high polarity. This study enhances understanding of hair analysis in doping investigations, providing insights into substance detectability.

2D/2D heterostructure Ni-Fe LDH/black phosphorus nanosheets with AuNP for noxious substance diphenylamine detection in food samples - Sanjay Ballur Prasanna; Yu-Chien Lin; Sayee Kannan Ramaraj; Udesh Dhawan; Xinke Liu; Ching-Wei Tung; Rajalakshmi Sakthivel; Ren-Jei Chung (Food Chemistry, 2024)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Accumulated Hepatic Steatosis Grades Predicted by T2*-IDEAL Fat Fraction - Chang-Hsien Liu; Hing-Chiu Chang; Yi-Jui Liu; Wei-Ching Lin; Chi-Feng Hsieh; Te-Pao Lin; Cheng-Hsuan Juan; William Tzu-Liang; Chun-Jung Juan (Journal of Medical and Biological Engineering, 2023)

Corrigendum to “PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet” [Toxicology and Applied Pharmacology, 470, (2023), 116557] - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

The biocompatibility and hemostatic efficacy of silk fibroin nanofibrils fabricated by Shear-Induced phase separation process - Po-Wen Lu; Yu-Tzu Wu; Liang-Yu Chang; Tzu-Wei Lu; Chonlachat Jaihao; Ching-Shuan Huang; Mo-Fei Murphy Chuang; Chunche Lin; Innie Chen; Agnese Brangule; Aleksej Zarkov; Aivaras Kareiva; et al. (Chemical Engineering Journal, 2023)

How does tourist learning affect destination attachment in nature-based tourism: Multiple mediations comparison and distal mediation analysis - Chung-Ching Huang; Wei-Rong Lin (Journal of Outdoor Recreation and Tourism, 2023)

Marine Collision Avoidance Route Planning Model for MASS Based on Domain-Based Predicted Area of Danger - Chao-Wei Lu; Chao-Kuang Hsueh; Yung-Lin Chuang; Ching-Ming Lai; Fuh-Shyong Yang (Journal of Marine Science and Engineering, 2023)
When the own ship encounters target ships in a close-quarter situation, an officer on watch needs to safely and timely alter the course of the vessel to avoid a collision. If ECDIS can automatically collect the navigation parameters and plot areas of collision as quasi-static obstruction areas, it will be much easier for seafarers to implement effective route planning. Hence, this study focuses on developing the MCARP model as a theoretical concept based on the DPAD model and LCD model. By operating the MCARP using ArcGIS, DPADs and several effective collision avoidance routes can be generated and imported into ECDIS based on AIS information at large scales and ample time. The graphic overlay of DPADs and effective routes on ECDIS can serve as a collision avoidance strategy reference for the personnel controlling maritime autonomous surface ships. Finally, different ships encountering situations were input into a Transas navigational simulator. The simulation results showed that own ship could avoid collisions with multiple target ships at distances larger than the preset collision avoidance distances, which also indicated that MCARP is practically feasible.

Cleanup of Cr(VI)-polluted groundwater using immobilized bacterial consortia via bioreduction mechanisms - Wei-Han Lin; Chih-Ching Chien; Jiun-Hau Ou; Ying-Liang Yu; Ssu-Ching Chen; Chih-Ming Kao (Journal of Environmental Management, 2023)

Regulating energy gap in Ir-based ionic complexes to generate near-infrared emissions: Application in solid-state light-emitting electrochemical cells - Yan-Ding Lin; Pei-Wan Hsiao; Wun-Yu Chen; Sih-Yu Wu; Wei-Min Zhang; Chin-Wei Lu; Hai-Ching Su (Chemical Engineering Journal, 2023)

Livistona chinensis Water Extract has the Potential to Repair Thioacetamide-Induced Liver Fibrosis in Mice - San-Ho Hung; Tzu-Hsuan Hsu; Chun-Shien Wu; Yi-Ping Lin; Ching-Ting Wei; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2023)

PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Ethanol production using the whole solid-state fermented sugarcane bagasse cultivated by Trichoderma reesei RUT-C30 supplemented with commercial cellulase - Ching An Lin; Cheng Cheng; Li Wei Chen; C. Will Chen; Kow Jen Duan (Biocatalysis and Agricultural Biotechnology, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Co-incidence of BA.1 and BA.2 at the start of Singapore's Omicron wave revealed by Community and University Campus wastewater surveillance - Feng Jun Desmond Chua; Se Yeon Kim; Eric Hill; Jia Wei Cai; Wei Lin Lee; Xiaoqiong Gu; Siti Aisyah Afri Affandi; Wee Chiew Germaine Kwok; Weijie Ng; Mats Leifels; Federica Armas; Franciscus Chandra; et al. (Science of The Total Environment, 2023)

Toward sustainable inland aquaculture: Coastal subsidence monitoring in Taiwan - Wei-Chia Hung; Cheinway Hwang; Luigi Tosi; Shao-Hung Lin; Pei-Ching Tsai; Yi-An Chen; Wei-Ji Wang; En-Cheng Li; Sihao Ge (Remote Sensing Applications: Society and Environment, 2023)

Assessing the ecosystem services provided by conventional and organic farmlands: A better outcome for organic farmlands? - Ching-Hua Hsieh; Hsing-Wei Lin; Wan-Yu Liu (Ecosystem Services, 2023)

Sleep disturbance in adults with untreated primary brain tumors: prevalence and impact on quality of life - Pei-Ching Lin; Pin-Yuan Chen; Kuo-Chen Wei; Jian-her Lin; Mei-Ru Lin; Huan-Chih Wang; Hsiao-Yean Chiu (Sleep and Biological Rhythms, 2023)

Juvenile and Trash Fish Excluder Device (JTED) for Taiwanese Bottom Trawl - Chao-Ching Chen; Hsin-Zong Lin; Kuo-Wei Lan (Fishes, 2023)
Juvenile and trash fish excluder devices (JTEDs) are used to mitigate the ecological impact of trawling. Trawling has a large ecological footprint in Taiwan. Thus, this study designed three JTEDs, which differed only in grid interval, for single boat bottom otter trawls that are commonly used in Taiwan. The designed JTEDs were tested in the waters off of Kaohsiung on a Kaohsiung-based bottom trawler, and the results were as follows. (1) At least 300 species were caught, and 189 of these species had little commercial value; their weight accounted for 52.5% of the total catch. (2) The three JTEDs had good exclusion performance. (3) The ratios of the weight of bycatch excluded to the weight of total catch were 7.9%, 29.1%, and 36.2%, for grid intervals of 10, 15, and 20 mm, respectively. (4) JTEDs with grid intervals of 10, 15, and 20 mm were associated with a 0.4%, 11.5%, and 19.0% loss in revenue, respectively. (5) Mature (and thus commercially valuable) Loliginidae tended to be excluded when the grid interval was 20 or (especially) 15 mm. In general, the designed JTEDs should be used at a grid size of 15 mm because this strikes the best balance between profitability and sustainability.

Centenarian clocks: epigenetic clocks for validating claims of exceptional longevity - Eric Dec; James Clement; Kaiyang Cheng; George M. Church; Michael B. Fossel; David H. Rehkopf; Luis Rosero-Bixby; Michael S. Kobor; David TS. Lin; Ake T. Lu; Zhe Fei; Wei Guo; et al. (GeroScience, 2023)
Claims surrounding exceptional longevity are sometimes disputed or dismissed for lack of credible evidence. Here, we present three DNA methylation-based age estimators (epigenetic clocks) for verifying age claims of centenarians. The three centenarian clocks were developed based on n = 7039 blood and saliva samples from individuals older than 40, including n = 184 samples from centenarians, 122 samples from semi-supercentenarians (aged 105 +), and 25 samples from supercentenarians (aged 110 +). The oldest individual was 115 years old. Our most accurate centenarian clock resulted from applying a neural network model to a training set composed of individuals older than 40. An epigenome-wide association study of age in different age groups revealed that age effects in young individuals (age < 40) are correlated ( r = 0.55) with age effects in old individuals (age > 90). We present a chromatin state analysis of age effects in centenarians. The centenarian clocks are expected to be useful for validating claims surrounding exceptional old age.

Health Risk of Infants Exposed to Lead and Mercury Through Breastfeeding - Yung-Chieh Lin; Wei-Hsiang Chang; Tsun-Ching Li; Osuke Iwata; Hsiu-Ling Chen (Exposure and Health, 2023)
Donor milk from the human milk bank is important for vulnerable infants without their mothers’ own milk. Longitudinal changes in toxic metals in donor milk has not been reported. This study aimed to assess the effect of donors’ demographic characteristics, life habits and dietary habits on the concentration of metals in breastmilk donated to a human milk bank and to assess the health risk of lead (Pb) and mercury (Hg) exposure of donor mothers’ offspring through breastfeeding and the vulnerable recipients. A total of 228 samples, which were longitudinally donated to the human milk bank by 39 donors, were selected specifically to assess the levels of Pb, Hg, and MeHg. Donors’ offspring were also enrolled as mother-infant-dyads to monthly obtain the milk consumption and body weight. The results showed significant differences in the infant risk in exclusive breastfeeding months. The average Pb level of breast milk was 6.49 ± 5.23 µg/L (mean ± standard deviation), and the Hg level was 0.76 ± 0.98 µg/L. The sources of these toxins—residential districts, cleaning products, cosmetics, drinking water, viscera, eggs, seafood, and canned food—have a significant influence on the concentration of toxic metals in human milk. This study showed an unacceptable non-cancerous health risk (95th percentile hazard index, HI = 1.37 > 1) for Pb and Hg. In the future, the breast milk offered by the bank should be strictly monitored, especial for Pb, to ensure high-quality donor milk for vulnerable recipients but also donor mothers’ offspring who depend on it. Graphical Abstract

Analyzing landslide-induced debris flow and flow-bridge interaction by using a hybrid model of depth-averaged model and discrete element method - Wen-Jie Shiu; Ching-Fang Lee; Chia-Chi Chiu; Meng-Chia Weng; Che-Ming Yang; Wei-An Chao; Chun-Yuan Liu; Cheng-Han Lin; Wei-Kai Huang (Landslides, 2023)

The Development and Characterization of a Highly Sensitive Mature TGFβ3 Assay to Evaluate Anti-TGFβ3 Target Engagement - A. Francesca Setiadi; Gizette Sperinde; Melissa Cheu; Wei-Ching Liang; WeiYu Lin; Connie Mahood; Saloumeh K. Fischer (The AAPS Journal, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

13.2% EQE near-infrared TADF OLED with emission peak at 761 nm - Jing-Wen Tai; Yukun Tang; Kai Zhang; Chen-Zong Yang; Ze-Hui Pan; Yu-Ching Lin; Yu-Wei Shih; Chia-Hsun Chen; Tien-Lung Chiu; Jiun-Haw Lee; Chuan-Kui Wang; Chung-Chih Wu; et al. (Chemical Engineering Journal, 2023)

Prediction of Groundwater Quality Using Seven Types of First-Order Univariate Grey Model in the Chishan Basin, Taiwan - Tzu-Yi Pai; Ray-Shyan Wu; Ching-Ho Chen; Huang-Mu Lo; Terng-Jou Wan; Min-Hsin Liu; Wei-Cheng Chen; Yi-Ping Lin; Chun-Tse Hsu (Water, Air, & Soil Pollution, 2022)

The Spatial Variation in Chlorophyte Community Composition From Coastal to Offshore Waters in a Subtropical Continental Shelf System - Yun-Chi Lin; Chien-Pang Chin; Wei-Ting Chen; Ching-Ting Huang; Gwo-Ching Gong; Kuo-Ping Chiang; Xin-Bei Chen (Frontiers in Marine Science, 2022)
Globally, the continental shelf occupies less than 10% of the total sea surface, but supports substantial primary production and fisheries. Photosynthetic picoeukaryotes (PPE) are important primary producers in marine ecosystems, and chlorophytes make a significant contribution to PPE abundance. Although the distribution of chlorophytes has been widely studied, little is known about how their community composition varies along the coastal-offshore gradient in subtropical continental shelf waters. To better understand their spatial variations, we employed metabarcoding data of 18S rRNA V4 gene to examine chlorophyte composition within the surface and deep chlorophyll maximum (DCM) layers over the continental shelf in the East China Sea (ECS) with high-resolution sampling. Our results indicate a higher chlorophyte diversity in the surface layer than in the DCM. In addition, we found that chlorophytes in oligotrophic Kuroshio surface water were the most diverse, with a higher percentage of Chloropicophyceae, prasinophyte clade V, prasinophyte clade IX, Palmophyllophyceae and Chlorodendrophyceae. In more eutrophic waters along the coast and within the DCM layer, chlorophytes were dominated by Mamiellophyceae. A significant spatial variation in community composition occurred along the nutrient gradient in the subtropical continental shelf ecosystem, varying from Mamiellophyceae-dominant in coastal water to Chloropicophyceae-dominant in offshore water. Furthermore, at a low saline coastal station, which had the lowest chlorophyte diversity, Picochlorum (Trebouxiophyceae) was dominant. Overall, chlorophyte diversity was positively correlated with temperature, and negatively correlated with silicate concentration. This study revealed that terrestrial input into continental systems influences chlorophyte diversity in the subtropical northwestern Pacific Ocean.

Preliminary establishment of a mass movement warning system for Taiwan using the soil water index - Chi-Wen Chen; Ching Hung; Guan-Wei Lin; Jun-Jih Liou; Shih-Yao Lin; Hsin-Chi Li; Yung-Ming Chen; Hongey Chen (Landslides, 2022)

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

Using DeepLab v3 + -based semantic segmentation to evaluate platelet activation - Tsung-Chen Kuo; Ting-Wei Cheng; Ching-Kai Lin; Ming-Che Chang; Kuang-Yao Cheng; Yun-Chien Cheng (Medical & Biological Engineering & Computing, 2022)

TREM-2 mediates dendritic cell–induced NO to suppress Th17 activation and ameliorate chronic kidney diseases - Ching-Cheng Lin; Ti-Yung Chang; Yong-Chen Lu; Yun-Syuan Wu; Wei Huang; Wei-Chi Lo; Guan-Fu Liu; Wei-Chan Hsu; Pamela S. Ohashi; Tak W. Mak; Jong-Ling Fuh; Hui-Chen Chen; et al. (Journal of Molecular Medicine, 2022)

Differences in the Composition of Abundant Marine Picoeukaryotes in the Marginal Sea Derived from Flooding - Chih-Ching Chung; Gwo-Ching Gong; Yun-Chi Lin; Ching-Wei Hsu (Frontiers in Marine Science, 2022)
The transient impact of flooding on the community composition of marine picoeukaryotes (PEs, cell size ≤5 μm) in the East China Sea (ECS) was revealed in this study. In a summer without flooding (i.e., July 2009), photosynthetic picoeukaryotes (PPEs) were more abundant in the area covered by the Changjiang River diluted water (CDW, salinity ≤31) than in the non-CDW affected area. According to the 18S ribosomal RNA phylogeny, Alveolata (all from the superclass Dinoflagellata) was the main community component accounting for 72 to 99% of the community at each sampling station during the nonflooded summer. In addition to Dinoflagellata, diatoms or Chlorophyta also contributed a considerable proportion to the PE assemblage at the stations close to the edge of CDW coverage. In July 2010, an extreme flooding event occurred in the Changjiang River basin and led to the CDW covering nearly half of the ECS. In the flooded summer, the abundance of PPEs in the CDW-covered area decreased significantly to less than 1 × 10 4 cells ml -1 . Compared to that during the nonflooded summer, the diversity of the PE composition was increased. While Dinophyceae still dominated the surface waters, Syndiniophyceae, which were represented by the uncultured Marine Alveolata Group (MALV)-I and MALV-II, accounted for a substantial amount in the Dinoflagellata superclass relative to this community composition in the nonflooded summer. Furthermore, a variety of plankton, including Cryptophyta, Haptophyta, Picobiliphyta, the uncultured Marine Stramenopiles (MASTs) and heterotrophic nanoflagellates, were observed. The nutrition modes of these PEs have been reported to be mixotrophic or heterotrophic. Therefore, it was inferred that the potentially mixotrophic and heterotrophic PE compositions might be favored in the marginal sea in the flooded summer.

Anti-inflammatory constituents from Phyllostachys makinoi Hayata - Chia-Ching Liaw; Yu-Chi Lin; Shao-Yu Wu; Jenny Chun-Ling Kuo; Zhi-Hu Lin; Kai-Wei Lin; Huang Hui-Chi; Li-Ming Yang Kuo; Yao-Haur Kuo (Natural Product Research, 2022)

Towards a rapid assessment of highway slope disasters by using multidisciplinary techniques - Meng-Chia Weng; Cheng-Han Lin; Wen-Jie Shiu; Wei-An Chao; Chia-Chi Chiu; Ching-Fang Lee; Wei-Kai Huang; Che-Ming Yang (Landslides, 2022)
Mega-earthquakes and extreme climate events accompanied by intrinsic fragile geology lead to numerous landslides along mountain highways in Taiwan, causing enormous life and economic losses. In this study, a system for rapid slope disaster information integration and assessment is proposed with the aim of providing information on landslide occurrence, failure mechanisms, and subsequent landslide-affected areas to the highway authority rapidly. The functionality of the proposed system is deployed into three units: (1) geohazard rapid report (GeoPORT I), (2) multidisciplinary geological survey report (GeoPORT II), and (3) site-specific landslide simulation report (GeoPORT III). After landslide occurrence, the seismology-based monitoring network rapidly provides the initial slope disaster information, including preliminary location, event magnitude, earthquake activity, and source dynamics, within an hour. Within 3 days of the landslide, a multidisciplinary geological survey is conducted to collect high-precision topographical, geological, and remote-sensing data to determine the possible failure mechanism. After integrating the aforementioned information, a full-scale three-dimensional landslide simulation based on the discrete element method is performed within 10 days to reveal the failure process and to identify the areas potentially affected by subsequent disasters through scenario modeling. Overall, the proposed system can promptly provide comprehensive and objective information to relevant authorities after the event occurrence for hazard assessment. The proposed system was validated using a landslide event in the Central Cross-Island Highway of Taiwan.

Streptococcus vaginalis sp. nov., a novel bacterial species isolated from vaginal swabs of a pregnant woman with diabetes - An-Shine Chao; Chiao-Yun Lin; Angel Chao; Yun-Shien Lee; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Yi-Sheng Chen (Archives of Microbiology, 2021)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

Shallow gas hydrates off southwest Taiwan and their mechanisms - Yin-Sheng Huang; Shu-Kun Hsu; Chih-Chieh Su; Andrew Tien-Shun Lin; Pai-Sen Yu; Nathalie Babonneau; Gueorgui Ratzov; Serge Lallemand; Pi-Chuen Huang; Shiao-Shan Lin; Jing-Yi Lin; Kuo-Yen Wei; et al. (Marine Geophysical Research, 2021)
We have collected two shallow gas hydrate samples at two sites having different geological settings off southwest Taiwan during the cruise MD214 in 2018. The first core site, MD18-3542, is on the South Yuan-An East Ridge at ~ 1200 m water deep, where a structural unconformity covered by fine-silt sediments appears at ~ 5.5 m below the seafloor. The second core site, MD18-3543, is close to the Good-Weather Ridge at ~ 1100 m water deep, where a gas-related pockmark structure and authigenic carbonates are present at shallow strata with fine-silt sediments near the seafloor. Sediment properties of core MD18-3542 are distinctively different above and below the layer corresponding to the unconformity. Both cores show obvious gaps or voids in the lower core halves. The core features could be linked to the dissociated methane upward migrating from deep strata. Core site settings with upwelling methane would favor the formation of shallow gas hydrates. At site MD18-3542, the shallow hydrate could be formed due to high concentration methane kept beneath the unconformity covered by fine-silt sediments. At site MD18-3543, the shallow hydrate could be formed due to an extremely high flux of upwelling methane trapped either beneath the authigenic carbonates or fine-silt sediments.

Continental shelf morphology controlled by bottom currents, mud diapirism, and submarine slumping to the east of the Gaoping Canyon, off SW Taiwan - Yi-Ching Yeh; Chung-Lin Tsai; Shu-Kun Hsu; Hsiao-Shan Lin; Kuan-Ting Chen; Yen-Yu Cho; Chin-Wei Liang (Geo-Marine Letters, 2021)

Disinfection efficiency of hospital infectious disease wards with chlorine dioxide and hypochlorous acid - Ming-Chun Lu; Po-Lin Chen; Da-Ji Huang; Chih-Kuo Liang; Ching-Shan Hsu; Wei-Ting Liu (Aerobiologia, 2021)

Correction to: 4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay‑Huyen Chen; Ping‑Chen Shih; Han‑Yu Lin; Po‑Kai Wang; Po‑Ting Pan; Ching‑Wei Chuang; Ming‑Chang Kao (Inflammopharmacology, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Calycosin Preserves BDNF/TrkB Signaling and Reduces Post-Stroke Neurological Injury after Cerebral Ischemia by Reducing Accumulation of Hypertrophic and TNF-α-Containing Microglia in Rats - Chien-Chin Hsu; Ting-Wei Kuo; Wen-Pin Liu; Ching-Ping Chang; Hung-Jung Lin (Journal of Neuroimmune Pharmacology, 2020)

Twist1 Plays an Anti-apoptotic Role in Mutant Huntingtin Expression Striatal Progenitor Cells - Wei-Ping Jen; Hui-Mei Chen; Yow-Sien Lin; Yijuang Chern; Yi-Ching Lee (Molecular Neurobiology, 2020)

Strictly Lobar Cerebral Microbleeds Are Associated with Increased White Matter Volume - Pei-Ning Wang; Kun-Hsien Chou; Li-Ning Peng; Li-Kuo Liu; Wei-Ju Lee; Liang-Kung Chen; Ching-Po Lin; Chih-Ping Chung (Translational Stroke Research, 2020)

A multidecadal change analysis for irrigation ponds in Taoyuan, Taiwan, using multisource data - Yen-Ching Chen; Wei-Chun Lin; Lin-Hsuan Hsiao; Ke-Sheng Cheng (Paddy and Water Environment, 2020)

Tropical cyclone sensitivities to CO2 doubling: roles of atmospheric resolution, synoptic variability and background climate changes - Gabriel A. Vecchi; Thomas L. Delworth; Hiroyuki Murakami; Seth D. Underwood; Andrew T. Wittenberg; Fanrong Zeng; Wei Zhang; Jane W. Baldwin; Kieran T. Bhatia; William Cooke; Jie He; Sarah B. Kapnick; et al. (Climate Dynamics, 2019)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

Movement behaviour of released wild and farm-raised dolphinfish Coryphaena hippurus tracked by pop-up satellite archival tags - Shian-Jhong Lin; Michael K. Musyl; Sheng-Ping Wang; Nan-Jay Su; Wei-Chuan Chiang; Ching-Ping Lu; Kazuki Tone; Chang-Ying Wu; Akira Sasaki; Itsumi Nakamura; Kazuyoshi Komeyama; Ryo Kawabe (Fisheries Science, 2019)

Extracting region-specific runout behavior and rainfall thresholds for massive landslides using seismic records: a case study in southern Taiwan - Ching Hung; Guan-Wei Lin; Ben Leshchinsky; Hsien-Li Kuo (Bulletin of Engineering Geology and the Environment, 2019)

4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay-Huyen Chen; Ping-Chen Shih; Han-Yu Lin; Po-Kai Wang; Po-Ting Pan; Ching-Wei Chuang; Ming-Chang Kao (Inflammopharmacology, 2019)

High Circulatory Phosphate Level Is Associated with Cerebral Small-Vessel Diseases - Chih-Ping Chung; Li-Ning Peng; Kun-Hsien Chou; Li-Kuo Liu; Wei-Ju Lee; Ching-Po Lin; Liang-Kung Chen; Pei-Ning Wang (Translational Stroke Research, 2019)

Potassium Stimulation of IAA Transport Mediated by the Arabidopsis Importer AUX1 Investigated in a Heterologous Yeast System - Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Shih-Ming Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2019)

Modeling Alzheimer’s Disease by Induced Pluripotent Stem Cells Carrying APP D678H Mutation - Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Ching-Chang Huang; Jia-Li Lin; Yi-Jing Chen; Pei-Chi Wei; Yen-Shi Lo; Chin-Fa Yao; Ming-Wei Kuo; Chiung-Mei Chen (Molecular Neurobiology, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

The Aso-Bridge coseismic landslide: a numerical investigation of failure and runout behavior using finite and discrete element methods - Ching Hung; Chih-Hsuan Liu; Guan-Wei Lin; Ben Leshchinsky (Bulletin of Engineering Geology and the Environment, 2019)

Far-infrared Radiation Improves Motor Dysfunction and Neuropathology in Spinocerebellar Ataxia Type 3 Mice - Shin-Wu Liu; Jui-Chih Chang; Sheng-Fei Chuang; Ko-Hung Liu; Wen-Ling Cheng; Hui-Ju Chang; Huei-Shin Chang; Ta-Tsung Lin; Ching-Liang Hsieh; Wei-Yong Lin; Mingli Hsieh; Shou-Jen Kuo; et al. (The Cerebellum, 2019)

Evaluation of an enhanced FS method for finding the initiation time of earthquake-induced landslides - Guan-Wei Lin; Ching Hung; Huei-Sian Syu (Bulletin of Engineering Geology and the Environment, 2019)

Analysis of the Aso-Bridge landslide during the 2016 Kumamoto earthquakes in Japan - Ching Hung; Guan-Wei Lin; Huei-Sian Syu; Chi-Wen Chen; Hsin-Yi Yen (Bulletin of Engineering Geology and the Environment, 2018)

Occurrence of Emerging Contaminants in Aquaculture Waters: Cross-Contamination between Aquaculture Systems and Surrounding Waters - Webber Wei-Po Lai; Yen-Ching Lin; Yu-Hsiang Wang; Yue Leon Guo; Angela Yu-Chen Lin (Water, Air, & Soil Pollution, 2018)

D-Cycloserine Ameliorates Autism-Like Deficits by Removing GluA2-Containing AMPA Receptors in a Valproic Acid-Induced Rat Model - Han-Fang Wu; Po See Chen; Ya-Ting Hsu; Chi-Wei Lee; Tzu-Feng Wang; Yi-Ju Chen; Hui-Ching Lin (Molecular Neurobiology, 2018)

Prototype Deep Brain Stimulation System with Closed-Loop Control Feedback for Modulating Bladder Functions in Traumatic Brain Injured Animals - En Jen; Chii-Wann Lin; Tsung-Hsun Hsieh; Yi-Chun Chiu; Tsung-Che Lu; Shih-Ching Chen; Meng-Chao Chen; Chih-Wei Peng (Journal of Medical and Biological Engineering, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

Recent updates on phthalate exposure and human health: a special focus on liver toxicity and stem cell regeneration - Sarva Mangala Praveena; Seoh Wei Teh; Ranjith Kumar Rajendran; Narayanan Kannan; Chu-Ching Lin; Rozaini Abdullah; Suresh Kumar (Environmental Science and Pollution Research, 2018)

Tamoxifen usage correlates with increased risk of Parkinson’s disease in older women with breast cancer: a case–control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2018)

Prevalence, mechanisms and genetic relatedness of the human pathogenic fungus Aspergillus fumigatus exhibiting resistance to medical azoles in the environment of Taiwan - Hsuan‐Chen Wang; Jui‐Chang Huang; Yong‐Hong Lin; Yu‐Hsin Chen; Ming‐I Hsieh; Pui‐Ching Choi; Hsiu‐Jung Lo; Wei‐Lun Liu; Ching‐Shan Hsu; Hsin‐I Shih; Chi‐Jung Wu; Yee‐Chun Chen (Environmental Microbiology, 2018)
Summary Emerging azole resistance in Aspergillus fumigatus poses a serious threat to human health. This nationwide surveillance study investigated the prevalence and molecular characteristics of azole‐resistant A. fumigatus environmental isolates in Taiwan, an island country with increasing use of azole fungicides. Of the 2760 air and soil samples screened from 2014 to 2016, 451 A. fumigatus isolates were recovered from 266 samples and 34 isolates from 29 samples displayed resistance to medical azoles (itraconazole, voriconazole or posaconazole). The resistance prevalence was 10.9% and 7.5% in A. fumigatus ‐positive samples and isolates respectively. Most (29, 85.3%) azole‐resistant isolates harboured TR 34 /L98H mutations, which were widely distributed, clustered genetically with clinical isolates, and had growth rates that were similar to those of the wild‐type isolates. Microsatellite genotyping revealed both the global spread of the TR 34 /L98H isolates and the occurrence of TR 34 /L98H/S297T/F495I isolates belonging to local microsatellite genotypes. AfuMDR3 and atrF , two efflux transporter genes, were constitutively upregulated in two individual resistant isolates without cyp51A mutations, highlighting their potential roles in azole resistance. These results emphasize the need for periodic environmental surveillance at the molecular level in regions in which azole fungicides are applied, and agricultural fungicide management strategies that generate less selective pressure should be investigated.

Association of use of selective serotonin reuptake inhibitors with risk of acute pancreatitis: a case-control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

Alleviation of N-Methyl-d-Aspartate Receptor-Dependent Long-Term Depression via Regulation of the Glycogen Synthase Kinase-3β Pathway in the Amygdala of a Valproic Acid-Induced Animal Model of Autism - Han-Fang Wu; Po See Chen; Yi-Ju Chen; Chi-Wei Lee; I-Tuan Chen; Hui-Ching Lin (Molecular Neurobiology, 2017)

Correlation between proton pump inhibitors and risk of pyogenic liver abscess - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

Effects of Porphyromonas gingivalis on Titanium Surface by Different Clinical Treatment - Nominzul Batsukh; Sheng Wei Feng; Wei Fang Lee; Sy-Jye Leu; Pei-Yo Tsai; Kuo-Ning Ho; Che Tong Lin; Ching-Hua Su; Wei-Jen Chang (Journal of Medical and Biological Engineering, 2017)

The relationship between plasma and urinary 8-hydroxy-2-deoxyguanosine biomarkers measured by liquid chromatography tandem mass spectrometry - Chung-Ching Wang; Wei-Liang Chen; Chien-Ming Lin; Ching-Huang Lai; Ching-Hui Loh; Hong-I Chen; Saou-Hsing Liou (Environmental Science and Pollution Research, 2016)

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells - Chun-Liang Tung; Yi-Jun Jian; Jyh-Cheng Chen; Tai-Jing Wang; Wen-Ching Chen; Hao-Yu Zheng; Po-Yuan Chang; Kai-Sheng Liao; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Maternal exposure to di-(2-ethylhexyl) phthalate exposure deregulates blood pressure, adiposity, cholesterol metabolism and social interaction in mouse offspring - Kuan-I Lee; Chin-Wei Chiang; Hui-Ching Lin; Jin-Feng Zhao; Cheng-Ta Li; Song-Kun Shyue; Tzong-Shyuan Lee (Archives of Toxicology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Combined effect of rice genotypes and soil characteristics on iron plaque formation related to Pb uptake by rice in paddy soils - Fang-Lin Li; Ching-Ming Yang; Chien-Hui Syu; Dar-Yuan Lee; Ben-Jei Tsuang; Kai-Wei Juang (Journal of Soils and Sediments, 2016)

Spatial optimization procedure for land-use arrangement in a community based on a human comfort perspective - Pei-Yuan Chen; Ching-Pin Tung; Wei-Chih Lin; Yuan-Hua Li (Paddy and Water Environment, 2016)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Intra-Colonial Functional Differentiation-Related Modulation of the Cellular Membrane in a Pocilloporid Coral Seriatopora caliendrum - Chuan-Ho Tang; Ping-Chang Ku; Ching-Yu Lin; Te-Hao Chen; Kuo-Hsin Lee; Shu-Hui Lee; Wei-Hsien Wang (Marine Biotechnology, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

Occurrence of pharmaceuticals, hormones, and perfluorinated compounds in groundwater in Taiwan - Yen-Ching Lin; Webber Wei-Po Lai; Hsin-hsin Tung; Angela Yu-Chen Lin (Environmental Monitoring and Assessment, 2015)

Methodology of disaster risk assessment for debris flows in a river basin - Ing-Jia Chiou; Ching-Ho Chen; Wei-Lin Liu; Shiao-Mei Huang; Yu-Min Chang (Stochastic Environmental Research and Risk Assessment, 2015)

Therapeutic Efficacy of Neuro AiD™ (MLC 601), a Traditional Chinese Medicine, in Experimental Traumatic Brain Injury - Ming-Che Tsai; Ching-Ping Chang; Syue-Wei Peng; Kai-Sheng Jhuang; Yi-Hsien Fang; Mao-Tsun Lin; Thomas Chang-Yao Tsao (Journal of Neuroimmune Pharmacology, 2015)

The Akt inhibitor MK-2206 enhances the cytotoxicity of paclitaxel (Taxol) and cisplatin in ovarian cancer cells - Ying-Hsi Lin; Bert Yu-Hung Chen; Wei-Ting Lai; Shao-Fu Wu; Jih-Hwa Guh; Ann-Lii Cheng; Lih-Ching Hsu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity - Yun-Ping Lim; Ching-Hao Cheng; Wei-Cheng Chen; Shih-Yu Chang; Dong-Zong Hung; Jih-Jung Chen; Lei Wan; Wei-Chih Ma; Yu-Hsien Lin; Cing-Yu Chen; Tsuyoshi Yokoi; Miki Nakajima; et al. (Archives of Toxicology, 2015)

Functional Investigation of Transmembrane Helix 3 in H+-Translocating Pyrophosphatase - Ching-Hung Lee; Yen-Wei Chen; Yun-Tzu Huang; Yih-Jiuan Pan; Chien-Hsien Lee; Shih-Ming Lin; Lin-Kun Huang; Yueh-Yu Lo; Yu-Fen Huang; Yu-Di Hsu; Shih-Chung Yen; Jenn-Kang Hwang; et al. (The Journal of Membrane Biology, 2013)

Pemetrexed downregulates ERCC1 expression and enhances cytotoxicity effected by resveratrol in human nonsmall cell lung cancer cells - Ruey-Shyang Chen; Jen-Chung Ko; Hsien-Chun Chiu; Ting-Yu Wo; Yi-Jhen Huang; Sheng-Chieh Tseng; Huang-Jen Chen; Yu-Ching Huang; Yi-Jun Jian; Wei-Ting Lee; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Design, synthesis, and evaluation of fluorescent cell-penetrating peptidic antagonists of Grb2-SH2 for targeting MCF-7 breast cancer cells - Yu-Cheng Hsiao; Chen-Yu Lee; Yi-Jhen Lin; Shu-Huai Tsai; Kee-Ching G. Jeng; Wei-Ting Chao; Feng-Di T. Lung (Medicinal Chemistry Research, 2013)

MicroRNA-210 targets antiapoptotic Bcl-2 expression and mediates hypoxia-induced apoptosis of neuroblastoma cells - Chung-Ching Chio; Jia-Wei Lin; Heien-An Cheng; Wen-Ta Chiu; Yuan-Hung Wang; Jhi-Joung Wang; Chung-Hsi Hsing; Ruei-Ming Chen (Archives of Toxicology, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

Lipopolysaccharide/adenosine triphosphate-mediated signal transduction in the regulation of NLRP3 protein expression and caspase-1-mediated interleukin-1β secretion - Pei-Chun Liao; Louis Kuoping Chao; Ju-Ching Chou; Wei-Chih Dong; Chien-Nan Lin; Chai-Yi Lin; Ann Chen; Shuk-Man Ka; Chen-Lung Ho; Kuo-Feng Hua (Inflammation Research, 2013)

Recombined sequences between the non-coding control regions of JC and BK viruses found in the urine of a renal transplantation patient - Yu-Ching Liaw; Cheng-Hsu Chen; Kuo-Hsiung Shu; Chiung-Yao Fang; Wei-Chih Ou; Pei-Lain Chen; Cheng-Huang Shen; Mien-Chun Lin; Deching Chang; Meilin Wang (Virus Genes, 2012)

Albumin prevents reactive oxygen species-induced mitochondrial damage, autophagy, and apoptosis during serum starvation - Shu-Yu Liu; Chia-Ling Chen; Tsan-Tzu Yang; Wei-Ching Huang; Chia-Yuan Hsieh; Wan-Jou Shen; Tsung-Ting Tsai; Chi-Chang Shieh; Chiou-Feng Lin (Apoptosis, 2012)

Caffeine’s effect on intermittent sprint cycling performance with different rest intervals - Chia-Lun Lee; Ching-Feng Cheng; Jung-Charng Lin; Hsin-Wei Huang (European Journal of Applied Physiology, 2012)

In vitro shoot induction and plant regeneration from flower buds in Paphiopedilum orchids - Yu-Ju Liao; Yu-Ching Tsai; Yung-Wei Sun; Ruey-Song Lin; Fang-Sheng Wu (In Vitro Cellular & Developmental Biology - Plant, 2011)

Assessing abalone growth inhibition risk to cadmium and silver by linking toxicokinetics/toxicodynamics and subcellular partitioning - Wei-Yu Chen; Yun-Ru Ju; Bo-Ching Chen; Jeng-Wei Tsai; Chia-Jung Lin; Chung-Min Liao (Ecotoxicology, 2011)

Using Seven Types of GM (1, 1) Model to Forecast Hourly Particulate Matter Concentration in Banciao City of Taiwan - Tzu-Yi Pai; Ching-Lin Ho; Shyh-Wei Chen; Huang-Mu Lo; Pao-Jui Sung; Shu-Wen Lin; Wei-Jia Lai; Shih-Chi Tseng; Shu-Ping Ciou; Jui-Ling Kuo; Jing-Tang Kao (Water, Air, & Soil Pollution, 2011)

Trace metal cycling in the surface water of the South China Sea: Vertical fluxes, composition, and sources - Tung-Yuan Ho; Wen-Chen Chou; Ching-Ling Wei; Fei-Jan Lin; George T. F. Wong; Hui-Ling Line (Limnology and Oceanography, 2010)
We deployed floating traps in the surface waters of the South China Sea on four occasions at depths of 30 m, 100 m, and 160 m from 2006 to 2007 to quantify vertical metal fluxes in the surface water and examine trace metal composition in the sinking particles to investigate their sources. The elements determined include 13 trace metals and 8 major elements. The fluxes for most of the bioactive elements at 30 m varied markedly during different seasons and strongly co‐varied with organic matter production, but the fluxes at 160 m were low and consistent under different seasons, showing that most of the elements were internally recycled in the surface water during productive seasons. Most of the bioactive trace metals in sinking particles were correlated with biogenic P, and their P‐normalized quotas were also strongly associated with lithogenic Al. The ratios of metals to Al and P for most of the bioactive trace metals were significantly higher than the ratios in lithogenic particles and than intracellular quotas in plankton, respectively, indicating that the trace metals in the sinking particles were abiogenic, nonlithogenic, and adsorbed on biogenic particles. The comparable fluxes between aeolian deposition and the sinking particles in the mixed layer demonstrate that the highly enriched trace metals in the sinking particles were attributed to input from anthropogenic aerosols. The coupling and transport of anthropogenic trace metals with biogenic particles in oceanic surface waters may be an important mechanism for trace metal cycling in global oceans.

Probiotic Lactobacillus casei Expressing Human Lactoferrin Elevates Antibacterial Activity in the Gastrointestinal Tract - Hsiao-Ling Chen; Yi-Wen Lai; Chua-Shun Chen; Te-Wei Chu; Willie Lin; Chih-Ching Yen; Ming-Fong Lin; Ming-Yu Tu; Chuan-Mu Chen (BioMetals, 2010)

Regeneration of soybean (Glycine max L. Merrill) through direct somatic embryogenesis from the immature embryonic shoot tip - Murugan Loganathan; Subbiyan Maruthasalam; Ling Yin Shiu; Wei Ching Lien; Wen Hwei Hsu; Pei Fang Lee; Chih Wen Yu; Chin Ho Lin (In Vitro Cellular & Developmental Biology - Plant, 2010)

Model analyses of visual biofeedback training for EEG-based brain-computer interface - Chih-Wei Chen; Ming-Shaung Ju; Yun-Nien Sun; Chou-Ching K. Lin (Journal of Computational Neuroscience, 2009)

Ameliorative effects of Vaccaria segetalis extract on osteopenia in ovariectomized rats - Chun-Ching Shih; Cheng-Hsiu Lin; Wei-Li Lin (Journal of Natural Medicines, 2009)

Development of a Methodology for Strategic Environmental Assessment: Application to the Assessment of Golf Course Installation Policy in Taiwan - Ching-Ho Chen; Ray-Shyan Wu; Wei-Lin Liu; Wen-Ray Su; Yu-Min Chang (Environmental Management, 2009)

Pravastatin attenuates carboplatin-induced cardiotoxicity via inhibition of oxidative stress associated apoptosis - Ching-Feng Cheng; Shu-Hui Juan; Jin-Jer Chen; Ying-Chi Chao; His-Hsien Chen; Wei-Shiung Lian; Chun-Yi Lu; Chung-I Chang; Ted-H Chiu; Heng Lin (Apoptosis, 2008)

Solubilization of inorganic phosphates and plant growth promotion by Aspergillus niger - Chun-Chao Chuang; Yu-Lin Kuo; Chen-Ching Chao; Wei-Liang Chao (Biology and Fertility of Soils, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Solubilization of inorganic phosphates and plant growth promotion by Aspergillus niger - Chun-Chao Chuang; Yu-Lin Kuo; Chen-Ching Chao; Wei-Liang Chao (Biology and Fertility of Soils, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Sustainable Water Quality Management Framework and a Strategy Planning System for a River Basin - Ching-Ho Chen; Wei-Lin Liu; Horng-Guang Leu (Environmental Management, 2006)

Induction of G2/M phase arrest and apoptosis by a novel enediyne derivative, THDA, in chronic myeloid leukemia (K562) cells - Zchong-Zcho Wu; Ching-Ming Chien; Sheng-Huei Yang; Yi-Hsiung Lin; Xiu-Wei Hu; Yu-Jhang Lu; Ming-Jung Wu; Shinne-Ren Lin (Molecular and Cellular Biochemistry, 2006)

Transgenic tomato plants expressing the Arabidopsis NPR1 gene display enhanced resistance to a spectrum of fungal and bacterial diseases - Wan-Chi Lin; Ching-Fang Lu; Jia-Wei Wu; Ming-Lung Cheng; Yu-Mei Lin; Ning-Sun Yang; Lowell Black; Sylvia K. Green; Jaw-Fen Wang; Chiu-Ping Cheng (Transgenic Research, 2004)

Microsatellite polymorphism in promoter of heme oxygenase-1 gene is associated with susceptibility to coronary artery disease in type 2 diabetic patients - Ying-Hwa Chen; Shing-Jong Lin; Ming-Wei Lin; Hui-Ling Tsai; San-San Kuo; Jaw-Wen Chen; Min-Ji Charng; Tao-Cheng Wu; Lung-Ching Chen; Philip Ding; Wen-Harn Pan; Yuh-Shan Jou; et al. (Human Genetics, 2002)

Natural Frequency Analysis of Periodontal Conditions in Human Anterior Teeth - Haw-Ming Huang; Sheng-Yang Lee; Ching-Ying Yeh; Mao-Sheng Wang; Wei-Jen Chang; Che-Tong Lin (Annals of Biomedical Engineering, 2001)